Enhancing dispersion stability of nano zinc oxide with rhamnolipids and evaluating antibacterial activity against harmful corn fungi - Niu, Ben; Qiao, Shan; Sun, Yiming; Niu, Yongwu (Frontiers in Microbiology, 2025)
ObjectiveZinc oxide nanoparticles (ZnONPs) have strong antifungal activity against major harmful fungi in corn kernels. However, due to the high surface energy prone to agglomeration, the residual synthetic surfactants from conventional chemical synthesis may trigger cytotoxicity, whereas rhamnolipids, as a green, safe, non-toxic, and easily degradable biosurfactant, can effectively regulate the size and morphology of zinc oxide nanoparticles, thereby enhancing their antifungal activity and dispersibility.Methods and resultsThe products were characterized by one-way experiments with nanoparticle size, zeta potential, ultraviolet-visible spectrum, transmission electron microscopy, Fourier transform infrared spectroscopy and X-ray diffraction to determine the optimization conditions. The results showed that when the concentration of RLs was 1.0 mg/mL, the reaction temperature was 60°C, the concentration of zinc acetate was 0.7 mol/L, and the calcination temperature was 500 °C, the average particle size of RLs-ZnONPs was smaller about 45-50 nm compared with that of the unmodified N-ZnONPs, which had good dispersion and high stability. The antifungal performance of RLs-ZnONPs was evaluated using spore germination rate, mycelial biomass inhibition rate, ergosterol content, and leakage of intracellular contents. It was observed that at a concentration of 4.096 mg/mL, RLs-ZnONPs inhibited the mycelial biomass of four types of fungi by over 76.14%. At the same concentration, spore germination inhibition rates for the same fungi exceeded 86.56%, which interfered with the metabolic activities of the spores and inhibited the germination process. Additionally, RLs-ZnONPs disrupted the stability and integrity of fungal cell membranes, leading to leakage of intracellular electrolytes, nucleic acids, and proteins, thereby suppressing fungal growth.ConclusionThese research findings indicate that rhamnolipids can significantly improve the dispersibility of nanoscale zinc oxide and effectively reduce its particle size, thereby substantially enhancing its antifungal activity.